Potential role of vitamin D receptor gene polymorphism in determining bone phenotype in young male athletes - Nakamura, O.; Ishii, T.; Ando, Y.; Amagai, H.; Oto, M.; Imafuji, T.; Tokuyama, K. (Journal of Applied Physiology, 2002)
The genetic difference among individuals partly explains variance in adaptive response to exercise through gene-environment interaction. The aim of this cross-sectional study was to evaluate the role of the vitamin D receptor (VDR) gene polymorphism, which locates at the translation initiation site, in the adaptations of bone to long-term impact loading. The VDR genotypes, as detected by endonuclease Fok I, and bone phenotypes of the lumbar spine and femoral neck were examined in 44 highly trained young male athletes and 44 age-matched nonathletic controls. As a whole, the athletes had a significantly higher bone mineral content resulting from a combination of increased volume and density at both sites than the controls. When the athletes were compared with the controls within each VDR genotype, however, the increased spinal volume was found only in the athletes with the FF but not in those with the Ff genotype("F" for the absence of the endonuclease Fok I restriction site and "f" for its presence). Differences in bone mineral content in the lumbar spine and femoral neck between the controls and the athletes were greater in subjects with FF than those with Ff. Our results suggest a gene-environment interaction in that the bone phenotypes in individuals with FF adapt to impact loading by producing stronger bone structure than those with the Ff do.